2001
DOI: 10.1182/blood.v97.12.3836
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fc receptor γ-chain in platelet glycoprotein Ib–mediated signaling

Abstract: Introductionvon Willebrand factor (vWF) is a multimeric protein that mediates platelet adhesion to exposed subendothelium at sites of vascular injury. The adhesive property of vWF is tightly regulated so that plasma vWF does not normally interact with circulating platelets. However, after vWF is activated by binding to damaged vessel walls, it serves to bridge the constituents of subendothelium to glycoprotein Ib (GPIb) on the membrane of circulating platelets. 1,2 Although much is known about the molecular ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
126
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(130 citation statements)
references
References 53 publications
1
126
1
2
Order By: Relevance
“…This leads to binding and phosphorylation of Syk and the ultimate activation of phospholipase C␥2 and other effector molecules. The binding of VWF to the GPIb-IX-V complex has also been shown to result in phosphorylation of FcR␥ (22). Finally, FcR␥ has been observed to physically associate with GPIb␣ after platelet stimulation with alboaggregin A, which binds to both GPIb␣ and GPVI (23).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This leads to binding and phosphorylation of Syk and the ultimate activation of phospholipase C␥2 and other effector molecules. The binding of VWF to the GPIb-IX-V complex has also been shown to result in phosphorylation of FcR␥ (22). Finally, FcR␥ has been observed to physically associate with GPIb␣ after platelet stimulation with alboaggregin A, which binds to both GPIb␣ and GPVI (23).…”
Section: Discussionmentioning
confidence: 94%
“…In fact, studies with other GPIb␣-specific toxins have raised the possibility of a role for FcR␥ in signal transduction initiated by engagement of the GPIb-IX-V complex. The physical proximity of the GPIb-IX-V complex, Fc␥ RIIA, and FcR␥ has been recorded, and there is evidence for functional interrelationships between these molecules (21,22). Cross-linking of the GPIb-IX-V complex and Fc␥ RIIA results in tyrosine phosphorylation of the immunoreceptor tyrosine-based activation motif in both Fc␥ RIIA and FcR␥ (21).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that phosphoinositide (PI) 3-kinase is linked to GPIb-IX-V, via 14-3-3x, and that src kinase is activated by engagement of GPIb-IX-V (1, 2, 26). Additional studies support a role for Fc receptor g-chain (FcRg) in GPIb-IX-Vdependent signalling, since GPIb-IX-V and FcRg are coprecipitated (27), and GPIb-dependent signals are altered in FcRg-deficient platelets (28). FcgRIIa is also associated with GPIb-IX-V (1).…”
Section: Gpib-ix-vmentioning
confidence: 99%
“…Dual receptor occupancy by these ligands could initiate signalling by cross-linking GPIb-IX-V and GPVI (and thus FcRg). Third, both GPIb-IX-V-and GPVI-mediated signaling may involve FcRg (27,28,36,38). FcRg directly associates with GPVI, supporting its surface expression.…”
Section: Co-association Of Gpib-ix-v and Gpvi?mentioning
confidence: 99%
“…Other receptors coupled to Fc receptors include GPVI, a collagen receptor (Berlanga 2000; GPIb-IX-V, a vWF receptor (Wu 2001, Arthur 2005; and potentially C-type lectin receptor-2 (CLEC-2), which has an as-yet unknown function in platelets (Gross 2006).…”
Section: Immunoglobulin Receptorsmentioning
confidence: 99%